The Role of Costumer Satisfaction in Mediating the Relationship Between Service Quality and Price on Costumer Loyalty - Nasib Nasib (Enrichment : Journal of Management, 2021)
The purposes of this research are to determine and analyze the role of service quality and price on customer loyalty with customer satisfaction as the intervening variable. The location of this research is in Binjai Hypermart. The population are all hypermart costumer with accidental sampling technique with 122 people as sample. The research analysis uses path analysis. The results of sub 1 analysis prove that service quality and price have a positive and significant effect on customer satisfaction. The results of sub 2 analysis prove that service quality and price have a positive and significant effect on customer loyalty through customer satisfaction.